Transport corridors of the Republic of Kazakhstan and prospects of their development. (Journal of Economic Research & Business Administration, 2016)
Kazakhstan is located in the center of Eurasia, in the midst of communication flow between Europe and Asia. The country has a huge transit potential. Further development of the country’s transit potential in the field of international transport, which has great importance for the development of the country’s economy and strengthen international ties, largely depends on the development from passing through the territory of Kazakhstan transport corridors and their branches. Considering potentially leading role of the country in development of the Euroasian transport, the government actively participates in the world integration processes, which purpose is strengthening of the international and regional trade and economic cooperation. This paper discusses the issues of the organization of international transit traffic in the Republic of Kazakhstan. The main rail and road corridors, an analysis of the quality of roads passing through the territory of the Republic of Kazakhstan are given in the article. The authors identify the significant problems that must be resolved for the subsequent efficient operation of the country’s transport system and prospects of development of the transport complex of the Republic of Kazakhstan.